2004
DOI: 10.1007/s12126-004-1007-2
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of religious coping in late life: Conceptualization, measurement, and links to well-being

Abstract: Most older adults report using religion as a resource in coping with the many challenges of late life. Until recently, our understanding of religion in coping was limited by studies utilizing unidimensional measures of religion, which did little to explain the power that religion seems to have for so many people. More recently, multiple facets of religious coping have been explored, along with the implications of their use for many populations, including older adults. In this paper, we examine approaches to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 90 publications
(61 reference statements)
3
40
1
2
Order By: Relevance
“…It is axiomatic that young women experience intense pressure regarding their looks, weight, and appearance, a worry felt as normative discontent (Rodin et al 1985) tantamount to a chronic crisis of self-doubt (Crisp 1980). For many people religion provides resources for coping with difficult situations (Emery and Pargament 2004), and young women higher in religiosity seem to cope better with the challenge of accepting their bodies in a culture that upholds narrow and unattainable body norms. In contrast to these psychological dynamics in young women, we speculate that after decades of normative dissatisfaction most older women (our sample averaged 74 years of age) have assimilated their body shape into their identity such that body dissatisfaction no longer constitutes as much of a crisis (Whitbourne and Skultety 2002).…”
Section: Education 02mentioning
confidence: 99%
See 1 more Smart Citation
“…It is axiomatic that young women experience intense pressure regarding their looks, weight, and appearance, a worry felt as normative discontent (Rodin et al 1985) tantamount to a chronic crisis of self-doubt (Crisp 1980). For many people religion provides resources for coping with difficult situations (Emery and Pargament 2004), and young women higher in religiosity seem to cope better with the challenge of accepting their bodies in a culture that upholds narrow and unattainable body norms. In contrast to these psychological dynamics in young women, we speculate that after decades of normative dissatisfaction most older women (our sample averaged 74 years of age) have assimilated their body shape into their identity such that body dissatisfaction no longer constitutes as much of a crisis (Whitbourne and Skultety 2002).…”
Section: Education 02mentioning
confidence: 99%
“…The reassurance provided by one's personal religiosity may be most potent when there is a discrepancy between broader cultural standards of attractiveness and one's own identity as an aging adult. Emery and Pargament (2004) have suggested that religion provides the aging individual with an identity that perseveres even when physical appearance or external circumstances change. More broadly, Masters (2008) has asserted that religions provide the faithful with something of a ''stress management program'' that reduces psychological stress and anxiety (Masters 2008, p. 106).…”
Section: Education 02mentioning
confidence: 99%
“…According to Hill and Pargament, although support networks, including family, can change over time, a religious convoy is a stable support. A similar idea was expressed by Emery and Pargament (2004) and Dillon, Wink, and Fay (2003), who were influenced by Iannaconne' s (1990) idea of religious human capital. Iannaconne proposed that a person invests in religion across the life span and, therefore, has more to draw on in later life when coping resources are needed.…”
mentioning
confidence: 67%
“…He may cry for rest, peace, and dignity, but he will get infusions, transfusions, a heart machine, or tracheotomy if necessary.- Kubler-Ross, 1969, p. 22 According to Burdette, Hill, and Moulton (2005) and Emery and Pargament (2004), religious concerns may be particularly important at the end of life, because it may have an impact on decisions regarding medical treatments. Religious and spiritual beliefs can affect decisions around prolonging life, do-not-resuscitate (DNR) instructions, hospice and palliative care, and physicianassisted suicide (PAS).…”
Section: End-of-life Decisionsmentioning
confidence: 99%
See 1 more Smart Citation